Semiconductor microchips and fabrication : a practical guide to theory and manufacturing - Lian, Yaguang (Hoboken, New Jersey : Wiley, 2022)
Semiconductor Microchips and Fabrication Advanced and highly illustrated guide to semiconductor manufacturing from an experienced industry insider Semiconductor Microchips and Fabrication is a practical yet advanced book on the theory, design, and manufacturing of semiconductor microchips that describes the process using the principles of physics and chemistry, fills in the knowledge gaps for professionals and students who need to know how manufacturing equipment works, and provides valuable suggestions and solutions to many problems that students or engineers often encounter in semiconductor processing, including useful experiment results to help in process work. The explanation of the semiconductor manufacturing process, and the equipment needed, is carried out based on the machines that are used in clean rooms over the world so readers understand how they can use the equipment to achieve their design and manufacturing ambitions. Combining theory with practice, all descriptions are carried out around the actual equipment and processes by way of a highly visual text, with illustrations including equipment pictures, manufacturing process schematics, and structures of semiconductor microchips. Sample topics covered in Semiconductor Microchips and Fabrication include: An introduction to basic concepts, such as impedance mismatch from plasma machines and theories, such as energy bands and Clausius-Clapeyron equation Basic knowledge used in semiconductor devices and manufacturing machines, including DC and AC circuits, electric fields, magnetic fields, resonant cavity, and the components used in the devices and machines Transistor and integrated circuits, including bipolar transistors, junction field effect transistors, and metal-semiconductor field effect transistors The main processes used in the manufacturing of microchips, including lithography, metallization, reactive-ion etching (RIE), plasma-enhanced chemical vapor deposition (PECVD), thermal oxidation and implantation, and more The skills in the design and problem solving of processes, such as how to design a dry etching recipe, and how to solve the micro-grass problems in Bosch process Through Semiconductor Microchips and Fabrication, readers can obtain the fundamental knowledge and skills of semiconductor manufacturing, which will help them better understand and use semiconductor technology to improve their product quality or project research. Before approaching this text, readers should have basic knowledge of physics, chemistry, and circuitry.
Keywords: Semiconductors; Semiconductor Physics; Electronic Materials; Electronic books